Update Breast Cancer 2020 Part 3 – Early Breast Cancer - Huober, Jens; Schneeweiss, Andreas; Hartkopf, Andreas D.; Müller, Volkmar; Lux, Michael P.; Janni, Wolfgang; Ettl, Johannes; Belleville, Erik; Thill, Marc; Fasching, Peter A.; Kolberg, Hans-Christian; Schulmeyer, Carla E.; Welslau, Manfred; Overkamp, Friedrich; Tesch, Hans; Fehm, Tanja N.; Lüftner, Diana; Schütz, Florian; Wöckel, Achim (Geburtshilfe und Frauenheilkunde, 2020)
The treatment of patients with early breast cancer has always been characterised by escalation by new therapies and de-escalation through identification of better treatment regimens or introduction of better tools to estimate prognosis. Efforts in some of these areas in the last few years have led to solid data. The results of the large studies of de-escalation through use of multi-gene tests are available, as are the results of some studies that investigated the new anti-HER2 substances T-DM1 and pertuzumab in the early treatment situation. Several large-scale studies examining the role of CDK4/6 inhibitors will soon be concluded so innovations can be anticipated in this area also. This review article will summarise and classify the results of the latest publications.Die Therapie von Patientinnen mit frühem Mammakarzinom war immer schon geprägt von Eskalation durch neue Therapien und Deeskalation durch Identifikation besserer Therapieschemata oder Einführung von besseren Werkzeugen zur Einschätzung der Prognose. Die Anstrengungen der letzten Jahre haben auf einigen dieser Gebiete zu einer soliden Datenlage geführt. Die Ergebnisse der großen Deeskalationsstudien durch Nutzung von Multi-Gen-Tests liegen ebenso vor wie die Ergebnisse einiger Studien, welche die neuen Anti-HER2-Substanzen T-DM1 und Pertuzumab in der frühen Therapiesituation untersucht haben. Mehrere groß angelegte Studien zur Untersuchung der Rolle der CDK4/6-Inhibitoren stehen kurz vor dem Abschluss, sodass auch in dieser Therapiesituation mit Neuerungen zu rechnen ist. Diese Übersichtsarbeit soll die Ergebnisse der neuesten Publikationen zusammenfassen und einordnen.
Keywords: early breast cancer; prevention; treatment; prognosis; immunotherapy; digital medicine